Will there be a worldwide recession? - Günter Weinert (Intereconomics, 1974)
In recent weeks, fears of a worldwide economic recession have become widespread because more and more symptoms appear that resemble those at the start of the great depression of 1929. However, wrong conclusions may be drawn from similar symptoms unless basic development trends as well as the differences in overall data and in functional relations are seen at the same time.
Keywords: 330; Stabilisation Policy